Safety, tolerability, pharmacodynamics and pharmacokinetics following once‐daily doses of BI 187004, an inhibitor of 11 beta‐hydroxysteroid dehydrogenase‐1, over 28 days in patients with type 2 diabetes mellitus and overweight or obesity. Issue 3 (22nd December 2022) - Bianzano, Susanna; Nordaby, Matias; Plum‐Mörschel, Leona; Peil, Barbara; Heise, Tim
Abstract: Aims: To study the oral 11 beta‐hydroxysteroid dehydrogenase‐1 (11β‐HSD1) inhibitor BI 187004 (NCT02150824), as monotherapy and in combination with metformin, versus placebo in patients with type 2 diabetes mellitus (T2DM) affected by overweight or obesity. Materials and Methods: This Phase II, randomized controlled trial investigated multiple rising doses of BI 187004 as monotherapy (Arm 1: 20, 80 or 240 mg) and in combination with metformin (Arm 2: 240 mg), in adults with T2DM and a body mass index of 28–40 kg/m 2 . Results: In total, 103 patients (Arm 1: n = 62, Arm 2: n = 41) were included in this study. BI 187004 was rapidly absorbed and exposure increased approximately dose‐dependently. Target engagement of 11β‐HSD1 was observed with near‐full inhibition of 11β‐HSD1 in the liver [decreased (5α‐tetrahydrocortisol + 5β‐tetrahydrocortisol)/tetrahydrocortisone ratio]; hypothalamic–pituitary–adrenal axis activation was also seen (increased total urinary corticosteroids). No clinically relevant changes from baseline with BI 187004 treatment were observed for bodyweight or meal tolerance test parameters, or in most efficacy endpoints testing glucose and lipid metabolism; a significant increase was observed in weighted mean plasma glucose ( p < .05 for 80 and 240 mg BI 187004) but not fasting plasma glucose. Drug‐related adverse events were reported for 14 patients (22.6%) in Arm 1 and 10 patients (24.4%) in Arm 2, most frequently headache, diarrhoea, flushing and dizziness. A dose‐dependent increase in heart rate was seen with BI 187004 treatment. Conclusions: BI 187004 was generally well tolerated in patients with T2DM. Despite complete 11β‐HSD1 inhibition, no clinically relevant effects were observed with BI 187004.